2022
DOI: 10.1111/manc.12411
|View full text |Cite
|
Sign up to set email alerts
|

Fee versus royalty licensing in a Cournot duopoly with increasing marginal costs

Abstract: We consider a symmetric homogeneous Cournot duopoly operating under increasing marginal costs. One of the firms owns a patented superior technology that reduces the intercept of the marginal cost function. We compare the incentives of the insider patentee to license the technology to the rival firm either through a fixed fee or through a royalty. We obtain that royalty licensing does not necessarily dominates in our setting: when decreasing returns are important, a royalty is superior only for small enough inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Moreover, many scholars have conducted studies to various internal factors. For example, Fauli‐Oller and Sandonís (2022) showed that royalty is only superior to fixed‐fee licenses in small innovations when diminishing returns become important. Hong et al (2022) found that, in addition to innovativeness of patentees, absorptive capacity of licensees may significantly affect licensing strategy and patentees may prefer unit royalty licenses and two‐part ad valorem licenses to fixed‐fee licensing contracts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, many scholars have conducted studies to various internal factors. For example, Fauli‐Oller and Sandonís (2022) showed that royalty is only superior to fixed‐fee licenses in small innovations when diminishing returns become important. Hong et al (2022) found that, in addition to innovativeness of patentees, absorptive capacity of licensees may significantly affect licensing strategy and patentees may prefer unit royalty licenses and two‐part ad valorem licenses to fixed‐fee licensing contracts.…”
Section: Literature Reviewmentioning
confidence: 99%